Participación y Motivación de los adultos mayores del Centro del Adulto Mayor Salaverry Essalud, 2021 - Carranza Quispe, Margarita Hortencia (2023)
The present investigation called "Participation and motivation of older adults at the Salaverry Essalud Senior Center, 2021", aims to analyze the influence of participation on the motivation of older adults at the Salaverry Essalud Senior Center, 2021. To carry out this research thesis, the different research methodologies were used, as well as the instruments to collect information that enriched the research, for which the interview and the survey were used, which allowed us to obtain qualitative and quantitative information. The sample population was made up of a total of 50 older adults enrolled in the CAM, the ages fluctuate between 60 and 87 years to whom the survey and interview were applied in order to gather information according to the variables participation and motivation in the adult. elderly. The results achieved show that motivation positively influences the active participation of the elderly, this motivation refers specifically to intrinsic motivation where it is evidenced through the interests, tastes and preferences of the elderly that promote their participation seeking their self-realization, in the same way. In this way, the family support, the sense of belonging and the adequate follow-up and monitoring that are promoted in your Institution positively influence the participation of the elderly to carry out the activities that are carried out in the CAM, thus carrying out successful aging.